2001
DOI: 10.1128/jcm.39.12.4349-4356.2001
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Isolated in Cases of Impetigo Produces Both Epidermolysin A or B and LukE-LukD in 78% of 131 Retrospective and Prospective Cases

Abstract: Clinical symptoms of impetigo and staphylococcal scalded skin syndrome may not only be expressed as the splitting of cell layers within the epidermis but are often accompanied by some localized inflammation. Toxin patterns of Staphylococcus aureus isolates originating from patients with impetigo and also from those with other primary and secondary skin infections in a retrospective isolate collection in France and a prospective isolate collection in French Guiana revealed a significant association (75% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 50 publications
3
45
0
8
Order By: Relevance
“…A complex family of virulence determinants of S. aureus is the bi-component pore-forming leukocidins which target leukocytes [24]. LukED, one toxin of this family, is mainly responsible for killing leukocyte cells by inducing Ca 2+ -activated transmembrane pores, thus plays a significant role in the ability of S. aureus to avoid host defenses [25][26][27]. Studies showed that LukED is associated with bloodstream infections, bullous impetigo and postantibiotic diarrhea [28].…”
Section: Discussionmentioning
confidence: 99%
“…A complex family of virulence determinants of S. aureus is the bi-component pore-forming leukocidins which target leukocytes [24]. LukED, one toxin of this family, is mainly responsible for killing leukocyte cells by inducing Ca 2+ -activated transmembrane pores, thus plays a significant role in the ability of S. aureus to avoid host defenses [25][26][27]. Studies showed that LukED is associated with bloodstream infections, bullous impetigo and postantibiotic diarrhea [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is some correlative evidence to suggest that LukED-producing strains are isolated at a greater frequency from patients with impetigo, antibiotic-associated diarrhea, furuncles, and invasive blood-borne infections (104,133,231,232). However, these studies were conducted when the lukED genes were believed to be present in ϳ30% of all S. aureus strains.…”
Section: Lukedmentioning
confidence: 99%
“…sea; selp; sea, selq, selk (Baba, Takeuchi et al 2002;McCarthy, Witney et al 2012) (Choorit, Kaneko et al 1995;Gravet, Couppie et al 2001;Kaneko and Kamio 2004;von Eiff, Friedrich et al 2004;Ventura, Malachowa et al 2010;Dumont, Nygaard et al 2011;Alonzo, Benson et al 2012;Rigby and DeLeo 2012;Vandenesch, Lina et al 2012) …”
Section: ) ɸSa3mentioning
confidence: 99%